Analisis Perlakuan Akuntansi Aset Biologis Pembibitan Kentang Berdasarkan SAK 241 pada CV Berkah Tani - Pitri Apiriyanti; Sri Galih Dewani; Sulfan Hedi; Ari Rudista; Yati Nurhajati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze accounting treatment for biological assets in potato seedling operations based on PSAK 241 at CV Berkah Tani in Kertasari District, Bandung Regency. The object of this study was selected because CV Berkah Tani’s business activities involve biological assets in the form of potato plants, which undergo biological transformation from the seedling stage to harvesting and therefore require accounting treatment that complies with applicable standards so that the financial statements reflect the company’s fair economic condition. This research uses a descriptive qualitative method with a case study approach. Data were collected through interviews, observation, and documentation, then analyzed using the interactive model of Miles and Huberman and validated through source and technique triangulation. The results show that the implementation of PSAK 241 at CV Berkah Tani has not yet been fully optimal, especially in terms of recognition, measurement, presentation, and disclosure of biological assets. The main constraints found are limited understanding of accounting standards, the absence of systematic recording, and difficulties in reliably determining the fair value of biological assets. Therefore, the implementation of PSAK 241 is needed to improve the quality of financial statements, transparency, and accountability in CV Berkah Tani’s management of potato seedling biological assets.